CEO pay cuts and forced turnover: Their causes and consequences - Gao, Huasheng (2013)
We study large discrete decreases in CEO pay and compare them to CEO forced turnover. The determinants are similar, as are the performance improvements after the action. After the pay cut, the CEO pay-for-performance sensitivity is abnormally high, such that the CEO can restore his pay level by reversing the poor performance. After either a pay cut or forced turnover, CEOs reduce investment and leverage, and improve performance, on average. Together, our results show that the possibility of these large compensation cuts provides ex ante incentives for CEOs to exert effort to avoid poor performance and that CEOs take actions to improve poor performance once pay is cut. The similarity of the causes and outcomes of large pay cuts compared to forced turnover suggests that large pay cuts are used as a substitute for forced turnover, helping to explain why forced turnover is rare.